The role of magmatism in the evolution of the Cambrian southern Oklahoma rift zone: geochemical constraints on the mafic-intermediate rocks in the Arbuckle Mountains, OK - Bulen, Casey L. (Kansas State University, 2012)
The Southern Oklahoma rift zone (SOA), which stretches from southern Oklahoma through the Texas panhandle and into Colorado and New Mexico, contains extensive bimodal mafic-silicic magmatism related to the opening of the Iapetus Ocean during the late Precambrian and early Cambrian. Within the SOA, the subsurface in and adjacent to the Arbuckle Mountains in southern Oklahoma contains thick packages of mafic to intermediate lava flows interlayered with thick, extensive rhyolite lava flows and lesser silicic intrusive bodies, which were first described during a 1982 drill test (Hamilton Brothers Turner Falls well) in the region. Well cuttings of these units were collected from that well and three others (Pan-Am Williams D-2, Pan-Am Jarman, Pan-Am Newberry). This study is focused on these mafic-intermediate lava flows, which represent an important stage in the evolution of the SOA and provide insights into the formation and tectonomagmatic evolution of the rift zone. The estimated 210,000 km[superscript]3 of mafic rocks in the SOA were extruded as a result of the break-up of Pannotia and the formation of the failed arm of a three-armed radial rift system. Samples analyzed from the wells plot as basalts to andesites on the TAS diagram of Le Bas et al (1986) and as subalkaline-alkaline basalts to andesite-trachyandesites on the Zr/TiO[subscript]2 vs. Nb/Y diagram of Winchester and Floyd (1977). They are dominantly tholeiitic on multiple discrimination diagrams including those of Miyashiro (1974) and Irvine and Baragar (1971). The lava flows contain traits common with EMI OIB coupled with upper crustal contamination, such as Zr/Nb values ranging from 8 to 10, Ba/Nb values ranging from 10 to 20, and K/Nb values ranging from 300 to 600. Chemostratigraphic comparisons between each well reveal up to five lava flow packages within the larger mafic-intermediate sequence, at least in the vicinity of the sampled wells. When compared with intrusive mafic rocks outcropped in the Wichita Mountains, the SOA lava flows display geochemical traits most similar to those of the Roosevelt Gabbros, suggesting a possible co-genetic relationship. Overall, the whole rock chemical characteristics coupled with comparisons with other large igneous provinces (Columbia River and Oregon Plateaus, East African Rift System) indicate that the SOA lava flows are the result of flood basalt volcanism.
Keywords: Southern Oklahoma rift zone; Basalts; Wichita province; Arbuckle Mountains; Large igneous province; Geology (0372)